Table_5_Innovation in Nucleotide-Binding Oligomerization-Like Receptor and Toll-Like Receptor Sensing Drives the Major Histocompatibility Complex-II Free Atlantic Cod Immune System.xlsx - Xingkun Jin; Bernat Morro; Ole K. Tørresen; Visila Moiche; Monica H. Solbakken; Kjetill S. Jakobsen; Sissel Jentoft; Simon MacKenzie (2020)
The absence of MHC class II antigen presentation and multiple pathogen recognition receptors in the Atlantic cod has not impaired its immune response however how underlying mechanisms have adapted remains largely unknown. In this study, ex vivo cod macrophages were challenged with various bacterial and viral microbe-associated molecular patterns (MAMP) to identify major response pathways. Cytosolic MAMP-PRR pathways based upon the NOD-like receptors (NLRs) and RIG-I-like receptors (RLRs) were identified as the critical response pathways. Our analyses suggest that internalization of exogenous ligands through scavenger receptors drives both pathways activating transcription factors like NF-kB (Nuclear factor-kappa B) and interferon regulatory factors (IRFs). Further, ligand-dependent differential expression of a unique TLR25 isoform and multiple NLR paralogues suggests (sub)neofunctionalization toward specific immune defensive strategies. Our results further demonstrate that the unique immune system of the Atlantic cod provides an unprecedented opportunity to explore the evolutionary history of PRR-based signaling in vertebrate immunity.